2017
DOI: 10.1002/2017gl075353
|View full text |Cite
|
Sign up to set email alerts
|

Midlatitude Summer Drying: An Underestimated Threat in CMIP5 Models?

Abstract: Early assessments of the hydrological impacts of global warming suggested both an intensification of the global water cycle and an expansion of dry areas. Yet these alarming conclusions were challenged by a number of latter studies emphasizing the lack of evidence in observations and historical simulations, as well as the large uncertainties in climate projections from the fifth phase of the Coupled Model Intercomparison Project (CMIP5). Here several aridity indices and a two‐tier attribution strategy are used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(48 citation statements)
references
References 33 publications
3
45
0
Order By: Relevance
“…Although during the last century only minor fire events have occurred in the CEL compared to other areas of the world, forest cover is expected to increase in the future and fuel will accumulate in widespread human-planted pine and spruce monocultures (Caudullo et al, 2016;Houston Durrant et al, 2016). Future climate change scenarios predict drier and warmer summers, and the frequency of natural ignition by lightning might increase (Douville and Plazzotta, 2017;Lhotka et al, 2018;Romps et al, 2014). These factors increase fire hazard and fire risk (Hardy, 2005), leading to a much more flammable landscape-a situation comparable to the early Holocene.…”
Section: Discussionmentioning
confidence: 99%
“…Although during the last century only minor fire events have occurred in the CEL compared to other areas of the world, forest cover is expected to increase in the future and fuel will accumulate in widespread human-planted pine and spruce monocultures (Caudullo et al, 2016;Houston Durrant et al, 2016). Future climate change scenarios predict drier and warmer summers, and the frequency of natural ignition by lightning might increase (Douville and Plazzotta, 2017;Lhotka et al, 2018;Romps et al, 2014). These factors increase fire hazard and fire risk (Hardy, 2005), leading to a much more flammable landscape-a situation comparable to the early Holocene.…”
Section: Discussionmentioning
confidence: 99%
“…24 Multimodel coupled CMIP5 simulations underestimate declining relative humidity observed over global land. 25,26 This discrepancy also applies to atmosphere-only experiments applying observed sea surface temperature (SST): a single model simulated a −0.05 to −0.25%/decade trend (1996-2015) compared with an observed estimate of −0.4 to −0.8%/decade. 25 It is not clear if this discrepancy is explained by potential deficiencies in representing ocean to land moisture transport, 27 land-atmosphere coupling, 24 or inhomogeneity of the observational records.…”
Section: Hydrological Sensitivity At the Global Scalementioning
confidence: 99%
“…It has been shown that most of the intermodel spread in wet extremes arises from tropical and subtropical regions (O'Gorman, 2012;O'Gorman & Schneider, 2009;Pendergrass & Hartmann, 2014b;Pfahl et al, 2017). Previous attempts to directly constrain projections in precipitation extremes are rather limited but have suggested that the increase in both wet and dry extremes, especially over land, may be underestimated by GCMs (Borodina et al, 2017;Douville & Plazzotta, 2017;O'Gorman, 2012).…”
Section: Introductionmentioning
confidence: 99%